(untitled) - Reid, James H. (Cambridge, UK,New York, 2003)
This comparison of the narrative techniques of two of the twentieth century's most important writers of prose combines theoretical analysis and text study of Proust's A la recherche du temps perdu and Beckett's trilogy of novels, Molloy, Malone dies, and The Unnamable. James Reid's study is an important contribution to the critical literature, and offers fresh perspectives on the crucial significance of the Recherche and the trilogy in the context of the twentieth-century novel
Keywords: Narration (rhetoric),Văn tường thuật (tu từ)